A parameterised mathematical model to elucidate osteoblast cell growth in a phosphate-glass microcarrier culture. (March 2019) - Burova, Iva; Peticone, Carlotta; De Silva Thompson, David; Knowles, Jonathan C; Wall, Ivan; Shipley, Rebecca J
Tissue engineering has the potential to augment bone grafting. Employing microcarriers as cell-expansion vehicles is a promising bottom-up bone tissue engineering strategy. Here we propose a collaborative approach between experimental work and mathematical modelling to develop protocols for growing microcarrier-based engineered constructs of clinically relevant size. Experiments in 96-well plates characterise cell growth with the model human cell line MG-63 using four phosphate glass microcarrier materials. Three of the materials are doped with 5 mol% TiO2 and contain 0%, 2% or 5% CoO, and the fourth material is doped only with 7% TiO2 (0% CoO). A mathematical model of cell growth is parameterised by finding material-specific growth coefficients through data-fitting against these experiments. The parameterised mathematical model offers more insight into the material performance by comparing culture outcome against clinically relevant criteria: maximising final cell number starting with the lowest cell number in the shortest time frame. Based on this analysis, material 7% TiO2 is identified as the most promising.